Alternative Ni-based cemented carbide binder – Hardness characterization by nano-indentation and focused ion beam. (June 2018) - Walbrühl, Martin; Linder, David; Ågren, John; Borgenstam, Annika
Abstract: The nano-hardness in the alternative 85 Ni- 15 Fe binder phase of WC cemented carbide has been investigated. High-resolution scanning electron microscopy (SEM) imaging was used to measure the projected indentation area and a general pile-up correction, confirmed on selected indents, has been employed using atomic force microscopy (AFM). Focused ion-beam (FIB) cross-sections have been used to investigate the binder morphology below the indentations and the local binder hardness has been associated to the distance to the surrounding WC grains. Generally, decreasing distance to the WC grains leads to increased binder hardness. Furthermore, the nano-hardness for the cemented carbide binder has been corrected for the indentation size effect (ISE) to obtain the corresponding macroscopic hardness. A solid solution strengthening model for multicomponent bulk alloys was used to calculate the expected binder Vickers hardness considering the binder solubilities of W and C. Both the strengthening model and the ISE corrected hardness values, for larger binder regions, are in good agreement indicating that the intrinsic binder phase hardness is similar to that of a bulk metal alloy with similar composition. Highlights: Experimental investigation of the binder hardness in alternative WC-Ni cemented carbide systems Consideration of the 3D binder morphology exposing the indents with focused ion beam (FIB) cross-sections Investigation of the confinement effect on the soft binder phase by the surrounding WC hard phase